Anti-poverty policies in Brazil: Reviewing the past ten years - Andrews, Christina W. [UNESP] (SAGE Publications, 2004)
This article reviews the main anti-poverty policies implemented in Brazil from the early 1990s to the early 2000s. These include focused and universal policies - such as education and health care - as well as the rural development, a 'middle ground' policy. Though the inter-municipal consortium, a new institutional arrangement gathering municipalities together, has emerged as a promising policy implementation tool, anti-poverty policies have faced implementation difficulties. Lack of coordination between different programs, even within the same policy area, has impaired their effectiveness. As a consequence, compensatory programs, based on monetary transfers to poor families, which face fewer implementation problems, have become the dominant type of anti-poverty policies in Brazil. Despite these shortcomings, a small Brazilian state, Santa Catarina, was able to reduce by 46 percent the number of individuals living in poverty in just ten years. This is a sign that fighting poverty can, after all, be a feasible endeavor. © 2004 IIAS, SAGE Publications (London, Thousand Oaks, CA and New Delhi).
Keywords: comparative study; poverty alleviation; social policy; strategic approach; Brazil; South America